Laporan Kasus: Pemeriksaan Tes PCR untuk SARS-CoV-2 Tetap Positif dengan Gejala Klinis Minimal di RSUD.Undata Palu, Sulawesi Tengah - Fitriyani, Indah; Wahyuni, Rosa Dwi; Lamadjido, Reny Arniwaty (Talenta Publisher, 2021)
Background: Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). SARS-CoV-2 is a new type of corona virus that has never been previously identified in humans. There are at least two types of coronavirus that are known to cause diseases that can cause severe symptoms, such as Middle East Respiratory Syndrome (MERS) and Severe Acute Respiratory Syndrome (SARS). WHO recommends molecular testing for all patients suspected of being infected with COVID-19. The recommended method is the molecular detection method / NAAT (Nucleic Acid Amplification Test) such as the RT-PCR examination. Objectives: To report a case of Covid 19 which focuses on laboratory examination problems. Case Illustration: A 27-year-old woman has a persistent high fever accompanied by pain in the joints, coughing, and also a rash on the face and all over the body. On the fourth day of fever, the sufferer loses his sense of smell and taste. Work history as a volunteer for medical personnel in the Covid (+) room. Discussion: Laboratory tests for the diagnosis of Covid 19 consist of a complete hematology examination, clinical chemical examination, immunological examination, molecular examination (RT-PCR), examination of SARS CoV-2 antibodies. Conclusion: In this patient, the results of the swab were still reactive even though the patient was no longer showing clinical symptoms. This indicates that the virus can still be detected through RT-PCR examination. Keywords: clinical symptoms, Covid 19 PCR test, SARS-CoV-2 Latar Belakang: Coronavirus Disease 2019 (COVID-19) adalah penyakit menular yang disebabkan oleh Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). SARS-CoV-2 merupakan corona virus jenis baru yang belum pernah diidentifikasi sebelumnya pada manusia. Ada setidaknya dua jenis corona virus yang diketahui menyebabkan penyakit yang dapat menimbulkan gejala berat seperti Middle East Respiratory Syndrome (MERS) dan Severe Acute Respiratory Syndrome (SARS). WHO merekomendasikan pemeriksaan molekuler untuk seluruh pasien yang terduga terinfeksi COVID-19. Metode yang dianjurkan adalah metode deteksi molekuler/NAAT (Nucleic Acid Amplification Test) seperti pemeriksaan RT-PCR. Tujuan: Melaporkan satu kasus Covid 19 yang menitikberatkan pada masalah pemeriksaan laboratorium. Ilustrasi Kasus: Seorang wanita usia 27 tahun mengalami demam tinggi terus menerus disertai nyeri pada persendian, batuk, dan juga timbul ruam di wajah dan seluruh badan. Hari ke empat demam, penderita mengalami kehilangan indra penciuman dan indra perasa. Riwayat kerja sebagai sukarela tenaga medis di ruangan Covid (+). Pembahasan: Pemeriksaan laboratorium untuk diagnosis Covid 19 terdiri dari pemeriksaan hematologi lengkap, pemeriksaan kimia klinik, pemeriksaan immunologi, pemeriksaan molekular (RT-PCR), pemeriksaan antibody SARS CoV-2. Kesimpulan: Pada pasien ini didapatkan hasil swab yang masih terus reaktif walaupun pasien sudah tidak lagi menunjukkan gejala klinis. Ini mengindikasikan bahwa virus masih dapat terdeteksi melalui pemeriksaan RT-PCR. Kata Kunci: gejala klinis, pemeriksaan PCR Covid 19, SARS-CoV-2